Laboratory environment monitoring and specimen transport robots - Yi-Chang Wu; Huan-Chun Wang (Institute of Advanced Engineering and Science, 2019)
Robots have been used in various areas to replace manpower, reduce costs, and facilitate more effective resource allocation. This study sought to assist the business of the bureau by developing two robots using the Robot Operating System. The developed robots have autonomous intelligent navigation functions and are suited to monitor the environment of the laboratories in the bureau. One robot had a temperature and humidity sensor and an infrared thermal camera, and it could be used to patrol and monitor the laboratory environment. The other robot had drawers in which specimens could be placed; robotic arm in the elevator could coordinate and control elevators, enabling the robot to move and transport specimens autonomously. Plenty of tests were conducted to verify the feasibility and practicality.